Expectations And Perceptions Of Guests Staying On Hotel Linen Cleanliness At Star Hotels In Berastagi Karo Regency - Robert Deffie (Politeknik Pariwisata Medan, 2021)
It is undeniable and inevitable that the provision of decent, clean, and comfortable hotel rooms becomes the expectations and perceptions of guests according to their wishes, the most important thing is also how the hotel can provide good and quality linen, clean, and free from dirt that attached. The approach and type of research based on a qualitative approach with the type of descriptive research. Sampling by purposive sampling with a sample of 38 hotel guest respondents at three four-star hotels, namely the Sibayak International Hotel, Rudang Hotel, and Green Garden Hotel. The approach and type of research based on a qualitative approach with the type of descriptive research. Sampling by purposive sampling with a sample of 38 hotel guest respondents at three four-star hotels, namely the Sibayak International Hotel, Rudang Hotel, and Green Garden Hotel. The results showed that the expectations of guests staying who were expecting factors in the average result of the research respondents were 21 people (55%), which indicated that clean, high quality, fresh hotel linens were visible. New (new), (crisp, and smooth (smooth) in Berastagi, Karo Regency are not suitable and do not meet the expectations of hotel guests while staying. The perception of guests staying overnight which includes perceptual aspects, namely the cognitive aspect with an average of 26 people or 68% quite good, the affective aspect on average 19 people (50%) getting a bad impression, and the conative aspect on average 18 people (47 %) is still not good. The cleanliness of hotel linens is averagely 19 people (50%) based on the expectations and perceptions of hotel guests who stay less than fulfilling in reality.